Validation of Two Screening Tools for Anxiety in Hemodialysis Patients - Nadort, Els; van Geenen, Noëlle J. K.; Schouten, Robbert W.; Boeschoten, Rosa E.; Chandie Shaw, Prataap; Vleming, Louis Jean; Schouten, Marcel; Farhat, Karima; Dekker, Friedo W.; van Oppen, Patricia; Siegert, Carl E. H.; Broekman, Birit F. P. (Journal of personalized medicine, 2022)
Background: Symptoms of anxiety are often unrecognized and untreated in dialysis patients. We investigated the diagnostic accuracy of two widely used screening tools for anxiety in hemodialysis patients. Methods: For this cross-sectional validation study, chronic hemodialysis patients from eight dialysis centers in the Netherlands were included. The Beck Anxiety Inventory (BAI) and Hospital Anxiety and Depression Scale—Anxiety subscale (HADS-A) were validated by the Mini International Neuropsychiatric Inventory (MINI) diagnostic interview. Receiver operating characteristic curves were used to determine the optimal cut-off values. Results: Of 65 participants, 13 (20%) were diagnosed with one or more anxiety disorders on the MINI, of which 5 were included in the analysis. ROC curves showed a good diagnostic accuracy of the BAI and HADS-A. The optimal cut-off value for the BAI was ≥13 (sensitivity 100%, specificity 85%) and for the HADS-A was ≥10 (sensitivity 80%, specificity 100%). Conclusions: Based on our limited data, both the BAI and the HADS-A seem to be valid screening instruments for anxiety in hemodialysis patients that can be used in routine dialysis care. The HADS-A consists of fewer items and showed fewer false-positive results than the BAI, which might make it more useful in clinical practice.